Relationship between Human Immunodeficiency Type 1 Infection and Expression of Human APOBEC3G and APOBEC3F - Ulenga, Nzovu K; Sarr, Abdoulaye Dieng; Thakore-Meloni, Seema; Sankalé, Jean-Louis; Eisen, Geoff; Kanki, Phyllis J (The Journal of infectious diseases, 2008)
Background. Human immunodeficiency virus type 1 (HIV-1)-infected individuals with a high viral set point progress to acquired immunodeficiency syndrome (AIDS) more rapidly than those with a low viral set point. It is not entirely clear which host and viral factors are responsible for the viral set point. Host factors that affect virus replication are likely to influence the viral set point. Human APOBEC proteins have been shown to restrict HIV-1 replication. Methods. This prospective study was conducted to determine the relationship between human APOBEC3G (hA3G) and APOBEC3F (hA3F) levels and the viral set point. Fourteen subjects were classified as having a high viral set point, and 16 were classified as having a low viral set point. We quantified the levels of hA3G and hA3F mRNA in HIV-1-infected, antiretroviral drug-naive individuals before and after infection. Results. We found a significant correlation between the hA3G mRNA level and the viral set point. The expression of hA3G and hA3F increased after infection, and the levels of hA3G and hA3F mRNA were significantly higher after infection in the low viral set point group, compared with the high viral set point group. Conclusions. The results suggest that the level of hA3G expression affects the establishment of the viral set point and may therefore function as a host determinant in the pathogenesis of HIV-1 infection.